Coronary Artery Bypass Grafting Combined with Mitral Valve Correction via Minimally Invasive Approach: Technique Description and Results - Dmytro Ye. Babliak; Oleksandr D. Babliak; Serhii V. Yatsuk (Український журнал серцево-судинної хірургії)
Aim. To present and analyze the technique of simultaneous coronary artery bypass grafting (CABG) and mitral valve repair or replacement through a minimally invasive approach—left anterior thoracotomy in the 4th intercostal space.